The role of continuous moderate-intensity exercise on increasing collagen density after tooth extraction - Irmawati, Anis; Melinda, Nadya; Tantiana; Azzaim, Yassir Ahmad; Balqis, Noor Faizah; Al-Tayar, Baher (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: The wound healing process post-extraction is expected to be quick, which can reduce the risk of complications and restore normal tissue function. A minimum oxygen supply needs to be met so that acceleration of the wound healing process can occur. Wound healing can be accelerated by continuous moderate-intensity exercise with increasing tissue oxygenation. Collagen requires oxygen in the procollagen formation process to support wound healing. Purpose: This study aimed to prove the role of continuous moderate-intensity exercise in increasing collagen density in the dental sockets of Wistar rats (Rattus norvegicus) after tooth extraction. Methods: Four groups of Wistar rats were created: control groups K1 (on day 3) and K2 (on day 7), and treatment groups K3 (on day 3) and K4 (on day 7). K1 and K2 were submerged in a bucket of water, and K3 and K4 received daily moderate-intensity exercise for a duration of two weeks. The rats' incisors were extracted on the day 15. Post-extraction collagen density was measured on day 3 (K1 and K3) and on day 7 (K2 and K4). The one-way ANOVA test and post-hoc Tukey test were used in the statistical analysis of the data. Results: There was a significant difference between all groups (p: 0.0001; p<0.05). Group K4 had a higher collagen density than the other groups. Conclusion: Continuous moderate-intensity exercise played a role in increasing the density of collagen in the rat tooth socket after tooth extraction.